A protease-cleavable liposome for co-delivery of anti-PD-L1 and doxorubicin for colon cancer therapy in mice - Yixuan Liu; Ying Xie; Yuling Chen; Jialun Duan; Chunjie Bao; Jinling Wang; Hexuan Feng; Mengjie Wang; Yuxin Ren; Peishan Li; Qian Luo; Jiarui Xu; et al. (Nature Communications)
Abstract Immune checkpoint blockade therapy using programmed cell death 1 (PD1) or programmed death ligand 1 (PD-L1) has made significant progress in the treatment of advanced cancers, with some patients achieving long-term remission without clinical recurrence. However, only a minority of colon cancer patients respond to the therapy. Here, we report a protease-cleavable anti-PD-L1 antibody liposome, eLipo anti-PD-L1, for enhancing colon cancer therapy. In vivo, eLipo anti-PD-L1 is cleaved by legumain at colon cancer site into pegylated anti-PD-L1 and cancer-homing doxorubicin liposome. Functional assessments show cancer-targeting, legumain-responding, tumor-penetrating, and immune-activating effects, as well as efficacy in treating colon cancer-bearing mice in vivo. Further mechanistic analysis implicates genes related to T cell differentiation and T cell receptor signaling as potential molecular mediators. Lastly, human colorectal cancer tissue evaluations verify expressions of PD-L1 and legumain, hinting a potential translatability. Our study thus suggests that eLipo anti-PD-L1 may be a feasible vector for co-delivery of immunochemotherapy for colon cancer.